Islamic Aspects Of Interest: Financing Strategy - Sadeghzadeh, Akbar (Accounting Department,, 2004)
Allah made trade lawful and forbade ribaâ€ (the Holy Quran 2:275). Islamic literature interprets â€œribaâ€ to â€œinterestâ€. Moslims perceive interest forbidden and avoid it. This affects adversely money and capital markets. ï¬scal and monetary policies. financing projects and eventually growth strategies and causes worse economic conditions of even rich Moslim countries. Many research projects, dealing with various aspects of rihu have been carried out aiming at ï¬nding a solution to the problem. Most of these pojects deal with deferral charges imposed on overdue loans, perceiving this charge as a penalty. hence legal; while some scholars declare it as unlawful and reject it. Interest, however, consists of three elements. These elements are: â€œtime value of money premium (Itvp)